On-Demand Network Management with NMaaS: Network Management as a Service - Kjorveziroski, Vojdan; Vuletic, Pavle V.; Lopatowski, Lukasz; Loui, Frederic (IEEE, 2022)
The need for network management is universal, no matter the size of the network. Unfortunately, monitoring is often burdensome for infrastructure teams, because despite catering to their production services, additional supporting systems need to be maintained, continuously updated, and configured. As a result of the ever-growing complexity of new network management solutions, the time required for testing a new tool is increasing, thus disincentivizing exploration of new alternatives. Network Management as a Service (NMaaS) is a software suite which allows teams to centrally manage multiple remote infrastructures through effortless, fast deployment and configuration of network management applications as well as supporting tools. Using the GitOps approach, all application configuration is versioned and automatically synced to running instances, allowing easy migration from existing installations, as well as roll-back of recent configuration changes. In this demonstration we outline the NMaaS architecture, discuss possible use-cases, and showcase the application deployment process together with the steps required for extending the existing application catalog.
“© 20XX IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.”
Keywords: Network Management; Containers; Kubernetes; GitOps; Orchestration